2013
DOI: 10.1021/ic402301u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Dipyrido-Annulated N-Heterocyclic Carbenes with Ortho Substituents

Abstract: A method for the introduction of various substituents at the 4 and 8 positions of 2,10-di-tert-butyldipyrido[1,2-c;2',1'-e]imidazolium salts, is described. The new imidazolium salts bearing substituents (R' = Cl, SPh) at the 4 and 8 positions are synthesized in three-step procedures, and carbenes generated from the imidazolium salts can be used to give the corresponding rhodium complexes. The role of the 4,8-substituents can be either bystanders or coordinating ligands according to the nature of the metal moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…and Kunz et al Both theoretical and experimental studies have shown that its aromatic dipyrido moieties contribute to empty p orbitals of the carbene carbon, resulting in a higher π-donating ability in comparison to Arduengo-type NHCs . Previously, we have successfully introduced thio, phosphinyl, and aryl substituents to the dpa NHC backbone. The aryl-substituted dpa Ar2 NHCs were in situ generated by deprotonation of the respective imidazolium salt and characterized by complexation to a gold­(I) center (Scheme ).…”
Section: Resultsmentioning
confidence: 98%
“…and Kunz et al Both theoretical and experimental studies have shown that its aromatic dipyrido moieties contribute to empty p orbitals of the carbene carbon, resulting in a higher π-donating ability in comparison to Arduengo-type NHCs . Previously, we have successfully introduced thio, phosphinyl, and aryl substituents to the dpa NHC backbone. The aryl-substituted dpa Ar2 NHCs were in situ generated by deprotonation of the respective imidazolium salt and characterized by complexation to a gold­(I) center (Scheme ).…”
Section: Resultsmentioning
confidence: 98%
“…The targeted salts shown in Scheme were synthesized from the thiourea 2 (Scheme ) 5b,5c. Via dilithiation by t BuLi, electrophilic addition of (BrCl 2 C) 2 followed by methylation using MeI, 2 was converted into the dibromo‐substituted species 8 in 85 % yield, which was sufficiently pure to be used without further purification.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, the ortho-diphosphinylsubstituted derivative (dpa P2 -NHC, Chart 1C) has only been characterized by coordination to a rhodium center previously. 34 This work reports the isolation and characterization of the dpa P2 -NHC for the first time. Its coordination chemistry to gold(I) complexes and the photoluminescent properties of the resulting multinuclear complexes are investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our group has successfully introduced thio, phosphinyl, and aryl groups into Weiss and Kunz’s dipyrido-annulated N-heterocyclic carbene (dpa-NHC) to form pincer ligands. The steric rigidity , and unusual weak σ-donating, π-rich, and overall strong donating nature of the backbone as carbene are of special interest to us. Among these, the ortho -diphosphinyl-substituted derivative (dpa P2 -NHC, Chart C) has only been characterized by coordination to a rhodium center previously …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation